The relationship between vertical jump power estimates and weightlifting ability: A field-test approach - Carlock, J. M.; Smith, S. L.; Hartman, M. J.; Morris, R. T.; Ciroslan, D. A.; Pierce, K. C.; Newton, R. U.; Harman, E. A.; Sands, W. A.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to assess the usefulness of the vertical jump and estimated vertical-jump power as a field test for weightlifting. Estimated PP output from the vertical jump was correlated with lifting ability among 64 USA national-level weightlifters (junior and senior men and women). Vertical jump was measured using the Kinematic Measurement System, consisting of a switch mat interfaced with a laptop computer. Vertical jumps were measured using a hands-on-hips method. A counter-movement vertical jump (CMJ) and a static vertical jump (SJ, 90° knee angle) were measured. Two trials were given for each condition. Test-retest reliability for jump height was intra-class correlation (ICC) = 0.98 (CMJ) and ICC = 0.96 (SJ). Athletes warmed up on their own for 2-3 minutes, followed by 2 practice jumps at each condition. Peak power (PP) was estimated using the equations developed by Sayers et al. (24). The athletes' current lifting capabilities were assessed by a questionnaire, and USA national coaches checked the listed values. Differences between groups (i.e., men versus women, juniors versus resident lifters) were determined using t-tests (p 0.05). Correlations were determined using Pearson's r. Results indicate that vertical jumping PP is strongly associated with weightlifting ability. Thus, these results indicate that PP derived from the vertical jump (CMJ or SJ) can be a valuable tool in assessing weightlifting performance.